2019
DOI: 10.1371/journal.pone.0227200
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic inhibition of ventral hippocampal neurons alleviates associative motor learning dysfunction in a rodent model of schizophrenia

Abstract: Schizophrenia (SZ) is a serious and incurable mental disorder characterized by clinical manifestations of positive and negative symptoms and cognitive dysfunction. High-frequency deep brain stimulation (DBS) of the ventral hippocampus (VHP) has been recently applied as a therapeutic approach for SZ in both experimental and clinical studies. However, little is known about the precise mechanism of VHP-DBS treatment for SZ and the role of hippocampal cell activation in the pathogenesis of SZ. With optogenetic tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…It has been reported that this conclusion is also applicable the GRA and SF in broccoli. Moreover, different organs of broccoli, including the seeds, seedlings, sprouts, leaves, and stalks, present quite different SF contents, which are mostly determined by the genotype and its interactions with the environment 22 , 40 44 . Similarly, in the florets and leaves that we analyzed, it was shown that there were significant variations in SF accumulation in different genotypes and organs at different developmental stages (florets at mature, buds to flowers at bolting) 3 , 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that this conclusion is also applicable the GRA and SF in broccoli. Moreover, different organs of broccoli, including the seeds, seedlings, sprouts, leaves, and stalks, present quite different SF contents, which are mostly determined by the genotype and its interactions with the environment 22 , 40 44 . Similarly, in the florets and leaves that we analyzed, it was shown that there were significant variations in SF accumulation in different genotypes and organs at different developmental stages (florets at mature, buds to flowers at bolting) 3 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“… 21 23 . GLS show great differences among different organs 20 , 22 , 24 . Therefore, the glucosinolate content depends not only on the genotype but also on the growing environment 2 , 25 .…”
Section: Introductionmentioning
confidence: 98%
“…Another disease awaiting the approval of initial clinical trials involving the application of optogenetic therapy and for which existing methods of treatment show limited effectiveness is urinary bladder syndrome [5]. Furthermore, many optogenetic studies conducted on animal models, such as rodents or nonhuman primates [6], were designed with the explicit goal of developing better targeted brain stimulation treatments for various psychiatric and neurological disorders in humans [7][8][9][10][11][12][13][14]. These attempts, along with rapid advancements in the field, demonstrate that optogenetics is already progressing towards clinical application.…”
Section: The Need For Further Neuroethical Debatementioning
confidence: 99%
“…Furthermore, to stimulate a targeted brain region efficiently, an implantable optogenetic device requires a sufficient light spread and intensity range and must be able to generate diverse illumination patterns (e.g., continuous illumination or short light pulses of changeable frequencies) and wavelengths suitable for activation of the targeted photosensory proteins of interest. 10 Until recently, neuronal illumination and recording of a neuron's evoked electrical signal required the insertion of two relatively large devices into the brain: fiber optic probes and so-called "optrodes" (fiber optics combined with electrodes). This procedure was highly invasive and characterized by increased tissue damage and declining optical output over time.…”
Section: Safety Issues and Technical Challengesmentioning
confidence: 99%
See 1 more Smart Citation